Microhardness of luting agents used for fiber post cementation submitted to thermo cycling - Zavanelli, Adriana Cristina [UNESP]; Quinelli Mazaro, Jose Vitor [UNESP]; Kian, Adriano T. [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP] (Incessant Nature Science Publishers, 2014)
Aims and Objectives: The aim of this study was to analyze the microhardness of three resin cements used in cementing glass fiber posts in bovine incisor. The microhardness was analyzed in cervical, middle and apical thirds before and after thermocycling process. Materials and Methods: Bovine teeth were instrumented and divided into 3 groups composed of 10 teeth each. Then, the teeth were sectioned and obturated and had their canals prepared at a depth of 12mm. Once proceeded the desobturation, the roots and glass fiber posts were prepared for adhesive cementation. After cementation, the microhardness reading was carried out. After initial reading, the samples were placed in a thermocycler and subjected to 2,000 cycles and a new microhardness reading. The data collected were subjected to analysis of variance (ANOVA) and Turkey’s test. Results: It was observed a statistical difference among the microhardness of resin cements. However, the statistical difference of microhardness before and after thermocycling appeared only in group U-200. Conclusion: Thermocycling reduced microhardness values in all cements evaluated in this study. The autopolymerizing cement Multilink presented the most stable microhardness mean values after thermocycling in the coronal, middle and apical thirds.
Keywords: Fiber posts; Microhardness; Resin cement; Thermocycling